Analysis Stability of the Tunnel # 11 Jakarta – Bandung High Speed Train Using Finite Element Method - Aprig Ustianto; Rizto Salia Zakri (Journals Mining Engineering : Bina Tambang, 2021)
Tunnel 11 has total length of 1,1 km. the shape of tunnel 11 was horseshoe with 15 meters wide and 13 meter high. Form classification rock mass rating (RMR) analysis, excavation recommendation on tunnel 11 by using full face method. Whereas actual excavation in the field with top heading and banching method. Based on the alignment required a plan of tunnel stability by using finite element. Analysis of tunnel’s stability using a full face excavation method based on RMR value. Tunnel stability with method of digging the top heading and bench and the optimized buffer based on the simulation carried out. The tunnel’s stability analysis is reviewed by the strenght factor and displacement value in the tunnel. Based on analysis with full face excavation method, on the left wall with no suport it’s got the lowest strenght factor value that is 6,3 and biggest displacement value that is 1,69 cm. with excavation on lower left side of the wall without support there was the smallest value of factor that is 5,2 and the biggest displacement value is 1,7 cm. strenght factor value by using full face excavation with top heading and benching threshold value strenght factor according to the KEPMEN 1827K/MEM/2018 and threshold deformation value according to japan society engineers ( JSCE ) based on a modeling simulation of the tunnel’s stability from economic side and stability analysis, then the optimal insulation on tunnel 11 is shotcrete K-175 #10 mm with top heading and benching excavation.